(The Effects of Traditional Extraction Methods and Storage on The Quality ofCrude Coconut Oil) - Shinta D. Sirait; Suci Widiyanti; Tatit K. Bunasor (Warta Industri Hasil Pertanian, 1996)
The effects of traditional extraction methods on the quality of crude coconut oil during storage had been studied.The extraction methods involved were:(a) by coconut milk evaporation to produce minyak klentik,and (b)by frying fresh shredded coconut meat prior pressing which produced minyak kampung (fry-dry oil).The results showed that the moisture content and the free fatty acids of both oils increased during storage.The peroxide value iniyially increased up to the maximum at the sixh to seventh week of storage then decreased,whereas the transmission of fry-dry oil worse than the other one,though panelist could not differenciate one from another.Preference test showed then the taste and after taste of fried cassava chips produced using fry-dry oil was prefered,however statistically both oils were acceptable up to the final storage (3 months).The quality characteristics of minyak klentik obtained had a moisture content of 0,01-0,64%,free fatty acid of 0,06-0,23%,a peroxide value of 0,41-5,80 mg oxigen /100 gr of oil and transmission of 97,25-88,25%.Whereas minyak kampung (fry-dry oil) ontained had a moisture content of oil and transmission of 88,50-79-75%.